Preparation and electrochemical characterization of lithium cobalt oxide nanoparticles by modified sol-gel method - Khomane, Ramdas B.; Agrawal, Amit C.; Kulkarni, B. D.; Gopukumar, S.; Sivashanmugam, A. (Materials Research Bulletin, 2008)
Uniformly distributed nanoparticles of LiCoO2 have been synthesized through the simple sol-gel method in presence of neutral surfactant (Tween-80). The powders were characterized by X-ray diffractometry, transmission electron microscopy and electrochemical method including charge-discharge cycling performance. The powder calcined at a temperature of 900 degrees C for 5 h shows pure phase layered LiCoO2. The results show that the particle size is reduced in presence of surfactant as compared to normal sol-gel method. Also, the sample prepared in presence of surfactant and calcined at 900 degrees C for 5 h shows the highest initial discharge capacity (106 mAh g(-1)) with good cycling stability as compared to the sample prepared without surfactant which shows the specific discharge capacity of 50 mAh g(-1). (C) 2007 Elsevier Ltd. All rights reserved.
Keywords: Electrochemical properties; intercalation reactions; Layered compounds; Sol-gel chemistry; X-ray diffraction

Functional delivery of siRNA in mice using dendriworms - Agrawal, Amit C.; Min, Dal-Hee; Singh, Neetu; Zhu, Haihao; Birjiniuk, Alona; von Maltzahn, Geoffrey; Harris, Todd J.; Xing, Deyin; Woolfenden, Stephen D.; Sharp, Phillip A.; Charest, Alain; Bhatia, Sangeeta N. (ACS Nano, 2009)

Effect of nanoparticle conjugation on gene silencing by RNA interference - Singh, Neetu; Agrawal, Amit C.; Leung, Anthony K. L.; Sharp, Phillip A.; Bhatia, Sangeeta N. (Journal of American Chemical Society, 2010)